2021
DOI: 10.1101/2021.09.03.458546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A separation-of-functionZIP4wheat mutant allows crossover between related chromosomes and is meiotically stable

Abstract: Many species, including most flowering plants, are polyploid, possessing multiple genomes. During polyploidisation, fertility is preserved via the evolution of mechanisms to control the behaviour of these multiple genomes during meiosis. On the polyploidisation of wheat, the major meiotic gene ZIP4 duplicated and diverged, with the resulting new gene TaZIP4-B2 being inserted into chromosome 5B. Previous studies showed that this TaZIP4-B2 promotes pairing and synapsis between wheat homologous chromosomes, whil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Possible candidates are genes in the mismatch repair pathway, which is implicated in the suppression of homoeologous crossovers through the detection of mismatches in the recombination intermediate heteroduplex (Bozdag et al., 2021; Serra et al., 2021; Spies & Fishel, 2015; Sugawara et al., 2004). Other candidates are genes encoding the ZMM proteins MSH4 and ZIP4, which promote recombination intermediate stability and have been shown to influence the formation of homoeologous crossovers in Brassica (Gonzalo et al., 2019) and wheat (Martín et al., 2021; Rey et al., 2017), respectively. None of these obvious candidates are within the BYS QTL, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible candidates are genes in the mismatch repair pathway, which is implicated in the suppression of homoeologous crossovers through the detection of mismatches in the recombination intermediate heteroduplex (Bozdag et al., 2021; Serra et al., 2021; Spies & Fishel, 2015; Sugawara et al., 2004). Other candidates are genes encoding the ZMM proteins MSH4 and ZIP4, which promote recombination intermediate stability and have been shown to influence the formation of homoeologous crossovers in Brassica (Gonzalo et al., 2019) and wheat (Martín et al., 2021; Rey et al., 2017), respectively. None of these obvious candidates are within the BYS QTL, however.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most significant of recent discoveries is the identification of the gene within the Ph1 locus in Triticum aestivum (wheat) responsible for suppressing homoeologous recombination. CRISPR mutagenesis demonstrated that TaZIP4‐B2 , an additional copy of ZIP4 within the Ph1 locus on chromosome 5B (three syntenic copies of ZIP4 are also present on chromosomes 3A, 3B and 3D), is responsible for the suppression of homoeologous crossovers in wheat and wheat hybrids (Martín et al., 2021; Rey et al., 2017). ZIP4 belongs to the ZMM group of proteins that bind to and stabilize meiotic recombination intermediates (Chelysheva et al., 2007; Lynn et al., 2007; Tsubouchi et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Non-Ph1-containing lines recombine homeologs as well as homologs, which results in multivalent formation, chromosome mis-segregation, and deleterious homeologous exchanges (Holm and Wang 1988). While the genetic behavior of Ph1 has been studied for decades, the mystery of its molecular identity was only recently solved: the Ph1 region is large and complex, but a (or the) causal gene seems to be a diverged extra copy of a gene encoding a ZMM group protein called ZIP4 (Rey et al 2017;Martín et al 2021). Like other ZMM proteins, ZIP4 is essential for Class I interfering crossover formation and defines crossover fate decisions early in pre-recombination maturation (Tsubouchi et al 2006;Lynn et al 2007;Shinohara et al 2008;Shen et al 2012).…”
Section: The Molecular Solution(s) To Allopolyploid Meiosismentioning
confidence: 99%